Biochemistry of Bacterial Biofilm: Insights into Antibiotic Resistance Mechanisms and Therapeutic Intervention - Kashish Azeem; Sadaf Fatima; Asghar Ali; Ayesha Ubaid; Fohad Mabood Husain; Mohammad Abid (Life)
Biofilms, composed of structured communities of bacteria embedded in a self-produced extracellular matrix, pose a significant challenge due to their heightened resistance to antibiotics and immune responses. This review highlights the mechanisms underpinning antibiotic resistance within bacterial biofilms, elucidating the adaptive strategies employed by microorganisms to withstand conventional antimicrobial agents. This encompasses the role of the extracellular matrix, altered gene expression, and the formation of persister cells, contributing to the recalcitrance of biofilms to eradication. A comprehensive understanding of these resistance mechanisms provides a for exploring innovative therapeutic interventions. This study explores promising avenues for future research, emphasizing the necessity of uncovering the specific genetic and phenotypic adaptations occurring within biofilms. The identification of vulnerabilities in biofilm architecture and the elucidation of key biofilm-specific targets emerge as crucial focal points for the development of targeted therapeutic strategies. In addressing the limitations of traditional antibiotics, this review discusses innovative therapeutic approaches. Nanomaterials with inherent antimicrobial properties, quorum-sensing inhibitors disrupting bacterial communication, and bacteriophages as biofilm-specific viral agents are highlighted as potential alternatives. The exploration of combination therapies, involving antimicrobial agents, biofilm-disrupting enzymes, and immunomodulators, is emphasized to enhance the efficacy of existing treatments and overcome biofilm resilience.